Competition, Technological Change and Productivity Gains: A Sectoral Analysis - Stéphane Ciriani; François Jeanjean (Intereconomics)
Abstract The empirical relationship between competition intensity and the rate of productivity growth across 30 sectors of the French economy between 1978 and 2015 displays an inverted U-shape. This implies that there exists an optimal level of competition for each sector, defined by the price markup that maximises the growth rate of hourly labour productivity. As there is a significant and strong positive correlation between optimal markups and technical progress rates in each sector, it follows that sectors with high technical progress require higher markups to maximise their labour productivity growth rate. The persistence of non-optimal markups in French sectors is associated with a 0.4% loss in aggregate annual labour productivity growth during the period (1.86%). French long-term productivity growth could have reached 2.25% had markups been at their optimal level. As a result, policies to foster innovation and productivity should aim at enabling the optimal level of markup (or market power), particularly in high-innovation sectors.